2014
DOI: 10.1002/2013gl058875
|View full text |Cite
|
Sign up to set email alerts
|

Summer mesospheric warmings and the quasi 2 day wave

Abstract: High‐altitude meteorological analyses are used to study the interannual variability of mesospheric weather in the Southern extratropics over five recent January's (2005, 2006, 2008, 2009, and 2010). Two features are apparent. First, there is significant variability in the quasi 2 day wave (Q2DW) with the largest amplitudes in January 2006 and also the last half of January 2005. Second, these periods coincide with high‐latitude temperature enhancements of 8–12 K. Previous studies have linked summer mesospheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
(53 reference statements)
3
23
0
Order By: Relevance
“…This may be attributable to strong variability in the summer hemisphere MLT region and may impact the IHC mechanism where the perturbations are needed to propagate through the mesosphere and lower thermosphere from the equator to the summer pole-a mechanism that remains unclear, as noted by Tan et al [2012] The summer mesospheric warmings may not be due solely to IHC. As noted by Pendlebury [2012] and Siskind and McCormack [2014], a strong westward drag by the QTDW in the summer hemisphere may partially negate the eastward GW drag that is seen climatologically atop the summer westward jet (e.g., Figures 5b and 6b). A diminished GW drag would reduce the summer polar upwelling and result in anomalous warming near the summer mesopause.…”
Section: Discussionmentioning
confidence: 78%
“…This may be attributable to strong variability in the summer hemisphere MLT region and may impact the IHC mechanism where the perturbations are needed to propagate through the mesosphere and lower thermosphere from the equator to the summer pole-a mechanism that remains unclear, as noted by Tan et al [2012] The summer mesospheric warmings may not be due solely to IHC. As noted by Pendlebury [2012] and Siskind and McCormack [2014], a strong westward drag by the QTDW in the summer hemisphere may partially negate the eastward GW drag that is seen climatologically atop the summer westward jet (e.g., Figures 5b and 6b). A diminished GW drag would reduce the summer polar upwelling and result in anomalous warming near the summer mesopause.…”
Section: Discussionmentioning
confidence: 78%
“…In large amplitude QTDW years, the brightness of southern PMC is reduced. Siskind and McCormack (2014) ascribe this effect to the QTDW depositing westward momentum that, acting through the Coriolis torque in Equation one, produces a southward flow that partially offsets the GW-driven equatorward, northward wind. Hence, there is a corresponding reduction in the upward motions at the pole with an accompanying reduction in the adiabatic cooling, leading to a temperature increase at the polar mesopause.…”
mentioning
confidence: 99%
“…Since variability in the summer stratospheric zonal flow is also related to the IHC mechanism, the two phenomena should be closely coupled, as suggested by Gu et al (2016). An indication of their interconnection is given by the following studies: (a) Karlsson et al (2007) found a strong anticorrelation between the noctilucent cloud occurrence and high-latitude winter stratospheric temperatures and (b) Siskind and McCormack (2014) sought revision of the theory behind the IHC since they could not find indications of the conventional temperature and wind patterns associated with the proposed IHC mechanism. In the light of these findings, we hypothesize that while the Q2DW is associated with an enhanced PW activity in the winter hemisphere as suggested by e.g.…”
Section: Introductionmentioning
confidence: 93%